ANALISIS KEBUTUHAN PENGEMBANGAN E-LKPD BERBASIS PBL UNTUK MEMFASILITASI KETERAMPILAN BERPIKIR KRITIS SISWA - Sari, Mustika; Stivani Suherman, Dea; Ratnawulan; Ulmi, Fauziah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the needs for developing a dynamics electronic student worksheet (E-SWS) based on the Problem-Based Learning (PBL) model to facilitate students' critical thinking skills. The study employed a descriptive research design using the 4D development model, with a particular focus on the define stage. The research instruments consisted of interview guidelines, a student characteristics questionnaire, and a critical thinking skills test. Data were analyzed using both qualitative and quantitative approaches. The findings revealed that technology-based instructional materials to support the improvement of students' critical thinking skills were not yet available. The average critical thinking score of the students was classified as very low, with a mean score of 50.88. The analysis of students' characteristics indicated generally positive results; however, these characteristics were not supported by the implementation of appropriate learning models and instructional materials, which contributed to their low critical thinking skills. Therefore, it can be concluded that the development of a PBL-based electronic student worksheet (E-SWS) is necessary to facilitate the improvement of students' critical thinking skills.